2005
DOI: 10.1161/01.hyp.0000157409.88971.fc
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of AT 1 Receptor Blocker, Olmesartan, and Estrogen on Atherosclerosis Via Anti-Oxidative Stress

Abstract: Abstracts-The present study explored the possibility that estrogen enhances the inhibitory effect of an angiotensin II type-1 (AT 1 ) receptor blocker (ARB), olmesartan, on atherosclerosis, focusing on oxidative stress using apolipoprotein E knockout mice (ApoEKO). After 6 weeks on a high-cholesterol diet, marked atherosclerotic lesion formation with an increase in oxidative stress, such as superoxide production, NAD(P)H oxidase activity and expression of p47 phox mRNA and rac-1 mRNA, were observed in the prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 43 publications
7
68
1
Order By: Relevance
“…17,18 Therefore, there is a possibility that progesterone plays some role in the enhancement of vascular remodeling in ovariectomized mice. However, our group has previously reported that increased neointimal formation, DNA synthesis, and atherosclerotic lesions in ovariectomized mice were reversed by treatment with estrogen to the physiologic (female) level, 9,10 suggesting that estrogen contributes to improvements in vascular remodeling over and above the apparent opposite effects of progesterone. The effect of ovariectomy on vascular remodeling was attenuated in Agtr2Ϫ mice, however, suggesting the possibility that estrogen could exert its vascular protective effects at least in part in concert with AT 2 receptor stimulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…17,18 Therefore, there is a possibility that progesterone plays some role in the enhancement of vascular remodeling in ovariectomized mice. However, our group has previously reported that increased neointimal formation, DNA synthesis, and atherosclerotic lesions in ovariectomized mice were reversed by treatment with estrogen to the physiologic (female) level, 9,10 suggesting that estrogen contributes to improvements in vascular remodeling over and above the apparent opposite effects of progesterone. The effect of ovariectomy on vascular remodeling was attenuated in Agtr2Ϫ mice, however, suggesting the possibility that estrogen could exert its vascular protective effects at least in part in concert with AT 2 receptor stimulation.…”
Section: Discussionmentioning
confidence: 98%
“…Estrogen concentration was measured as previously described 9,10 with an enzyme immunoassay kit (Cayman Chemical Inc). This assay is based on competition between free estradiol and an estradiol tracer for estradiol-specific rabbit antiserum binding sites.…”
Section: Measurement Of Plasma Estrogen Concentrationmentioning
confidence: 99%
“…This suggests that the activation of RAS may be independent of the abnormality of calcium metabolism. In vasculature, Horiuchi and colleagues 23,24 showed that estrogen antagonized Ang II signaling and Ang II induced atherosclerosis, which suggest that OVX might accelerate Ang II-induced signaling. Of importance, recent reports suggest that estrogen may enhance the ACE inhibition-mediated improvement of vascular remodeling in hypertension in female SHR with OVX through the inhibition of extracellular signal-regulated kinase 1/2.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we addressed this important point. It is well known that enhanced ROS production accelerates atherosclerosis and mono-therapy with an ARB or a CCB decrease ROS production in animal models (Tsuda et al 2005;Yamamoto et al 2008). The present study further demonstrates that the combination therapy with OLM plus AZL exerts additive anti-atherogenic effects in diabetic ApoE −/− mice, which could explain, at least in part, the beneficial effects of this combination therapy in humans (Kojima et al 2011).…”
Section: Anti-atherogenic Effects Of Olm Plus Azlmentioning
confidence: 99%